The G Protein-Coupled Estrogen Receptor (GPER): A Critical Therapeutic Target for Cancer - Keith A. Hall; Edward J. Filardo (Cells, 2023)
Estrogens have been implicated in the pathogenesis of various cancers, with increasing concern regarding the overall rising incidence of disease and exposure to environmental estrogens. Estrogens, both endogenous and environmental, manifest their actions through intracellular and plasma membrane receptors, named ERα, ERβ, and GPER. Collectively, they act to promote a broad transcriptional response that is mediated through multiple regulatory enhancers, including estrogen response elements (EREs), serum response elements (SREs), and cyclic AMP response elements (CREs). Yet, the design and rational assignment of antiestrogen therapy for breast cancer has strictly relied upon an endogenous estrogen–ER binary rubric that does not account for environmental estrogens or GPER. New endocrine therapies have focused on the development of drugs that degrade ER via ER complex destabilization or direct enzymatic ubiquitination. However, these new approaches do not broadly treat all cancer-involved receptors, including GPER. The latter is concerning since GPER is directly associated with tumor size, distant metastases, cancer stem cell activity, and endocrine resistance, indicating the importance of targeting this receptor to achieve a more complete therapeutic response. This review focuses on the critical importance and value of GPER-targeted therapeutics as part of a more holistic approach to the treatment of estrogen-driven malignancies.